Polymer nanocomposite foams - Lee, L.J.; Zeng, C; Cao, X.; Han, X.; Shen, J.; Xu, G.
Polymer nanocomposite foams have received increasingly attention in both scientific and industrial communities. The combination of functional nanoparticles and supercritical fluid foaming technology has a high potential to generate a new class of materials that are lightweight, high strength and multifunctional. A small amount of well-dispersed nanoparticles in the polymer domain may serve as the nucleation sites to facilitate the bubble nucleation process. Moreover, the nano-scaled particles are suitable for microscaled reinforcement, thus achieving the macroscopic mechanical enhancement. In this paper, we will first briefly review the synthesis and processing techniques of nanocomposites based on polymers that are important in the foam industry. Both thermoplastic and thermoset nanocomposite foams will be addressed. This is followed by an introduction of various foaming techniques. The effect of nanoparticles on the foam morphology and properties is then discussed. We conclude with the current and future trends of nanocomposite foams in both industrial and biomedical applications.
Keywords: POLYMER NANOCOMPOSITE; NANOCOMPOSITE FOAM; NUCLEATION; BUBBLE GROWTH; CELL SIZE; CELL DENSITY